Treatment Outcome and the Genetic Characteristics of Acute Promyelocytic Leukemia in Children in Poland From 2005 to 2018 - Czogała, Małgorzata; Pawińska-Wa̧sikowska, Katarzyna; Ksia̧żek, Teofila; Sikorska-Fic, Barbara; Matysiak, Michał; Rodziewicz-Konarska, Anna; Chybicka, Alicja; Skalska-Sadowska, Jolanta; Wachowiak, Jacek; Muszyńska-Rosłan, Katarzyna; Krawczuk-Rybak, Maryna; Grabowski, Dominik; et al. (Frontiers in Pediatrics, 2020)
Background: The aim of the study was analysis of the treatment outcome and genetic characteristics of acute promyelocytic leukemia (APL) in children in Poland from 2005 to 2018. Methods: All 41 patients diagnosed with APL in Poland in analyzed period were eligible for the study. In period I (2005-2015) 33 patients were treated with chemotherapy and all-trans retinoic acid (ATRA) and in period II (2015-2018) 3 patients (high risk) received induction chemotherapy with ATRA and arsenic trioxide (ATO) and 5 patients (standard risk) – ATRA and ATO without chemotherapy. Results: Probability of 5-years overall survival (OS), event free survival (EFS) and relapse free survival (RFS) were 0.819±0.069; 0.831± 0.063 and 0.961±0.037 respectively in whole cohort. Four (11%) early deaths were observed. One patient died of severe infection in course of disease progression. Relapse occurred in one patient, who died finally because of disease progression. All events occurred in the patients from the period I. Variant APL was identified in one patient (successfully treated with chemotherapy with ATRA) and complex translocation in one patient (the only patient with relapse). Additional chromosomal aberrations were found in 26% of patients, FLT3–ITD mutation was detected in 44% of patients, none of those changes influenced clinical outcome. Conclusion: Treatment outcome in analyzed group is similar to the results reported by other study groups. The main cause of deaths were coagulation disorders in early stage of disease. Early, accurate diagnosis followed by the specific treatment enables to reduce number of early deaths.